Use of Village Funds as an Effort to Improve the Economy of Fishermens Communities in Aceh Singkil Regency - Lestari, Yeni Sri; Liyana, Cut Irna; Abdillah, Ligar; Chadijah, Devi Intan; Khosihan, Aan (Department of Government Studies, Universitas Syiah Kuala, 2025)
This study examines the role of the Pulo Sarok Village Government in Aceh Singkil Regency in managing village funds to support fishermen's empowerment from a public policy perspective. The main focus is to analyze the effectiveness of implemented policies and the challenges encountered in the allocation and utilization of village funds, including limitations in human resources, constrained budgets, and low technological literacy among local fishermen. Using a qualitative approach, data were collected through in-depth interviews, field observations, and documentation of relevant policies. The findings indicate that although village funds are distributed regularly, their implementation remains suboptimal due to weak inter-agency coordination, limited oversight from the regency government, and low levels of community participation. Economic empowerment efforts have yet to show a significant impact on improving the fishermens welfare. This study highlights the importance of transparency in fund management, the strengthening of local human resource capacity, and synergy between village and regency governments to create sustainable policies that support the fisheries sector and the livelihoods of fishermen in Pulo Sarok Village.